1993
DOI: 10.1111/j.1460-2695.1993.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperature Fatigue Crack Growth in Alloy 718—part Ii: Effects of Environmental and Material Variables

Abstract: Observations concerning the effects of the environment and material variables on the crack growth process in alloy 718 are reviewed and analyzed on the basis of deformation characteristics in the crack tip region. The review of the role of material variables has focused on the effects of chemical composition and microstructure parameters including precipitate size and morphology as well as grain size and morphology. These analyses have suggested that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…For temperatures up to 650 o C, it was found that the main time-dependent process influencing fatigue crack propagation was grain boundary oxidation [5,6,7]. Hold times at maximum or minimum load in the fatigue cycle were found to significantly increase crack growth rates, with the dwell allowing time for oxide embrittlement of grain boundaries to occur [8][9][10][11][12][13][14]. Most of these studies were on long cracks using CT specimens, but the hold time effect has also been observed for pre-initiated cracks in Unotch specimens tested in bending [15].…”
Section: Introductionmentioning
confidence: 99%
“…For temperatures up to 650 o C, it was found that the main time-dependent process influencing fatigue crack propagation was grain boundary oxidation [5,6,7]. Hold times at maximum or minimum load in the fatigue cycle were found to significantly increase crack growth rates, with the dwell allowing time for oxide embrittlement of grain boundaries to occur [8][9][10][11][12][13][14]. Most of these studies were on long cracks using CT specimens, but the hold time effect has also been observed for pre-initiated cracks in Unotch specimens tested in bending [15].…”
Section: Introductionmentioning
confidence: 99%
“…Formation of intense slip bands and crack initiation along them is promoted by cyclic softening, with dislocations preferentially gliding along the softer band rather than in the harder surrounding regions [27,28] . IN718 is sensitive to the environment at elevated temperatures and grain boundary embrittlement by oxidation can occur [7,29,8] . Impingement of slip bands on grain boundaries produces local stress concentrations at the boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Cracks were observed to propagate along slip bands or along grain boundaries. Some intergranular propagation in IN718 is expected at 600 o C in air, because of oxidation embrittlement of grain boundaries [5,8,30] . In the Batch B Unotches, it is proposed that surface crack propagation of the crack along slip bands and grain boundaries produced a longer, more tortuous crack path, resulting in partial shielding of the crack from the applied stresses and hence a lower crack propagation rate.…”
Section: Discussionmentioning
confidence: 99%
“…A segment of these studies has focused on the crack growth correlations with grain boundary (GB) phases and ' precipitates within the  matrix [1][2][3]. These precipitates are quantified in terms of primary (' p ), secondary (' s ) and tertiary (' t ) gamma prime.…”
Section: Introductionmentioning
confidence: 99%